Penerapan Media Interaktif Berbasis Digital untuk Meningkatkan Motivasi Belajar Siswa SMP Negeri 6 Kerinci Kanan - Samsuir, Samsuir; Dewi , Fatni; Wirdanis , Eti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of digital interactive media in improving students' learning motivation at SMP Negeri 6 Kerinci Kanan. This research employs a Classroom Action Research (CAR) method conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 32 eighth-grade students. Data collection techniques included learning motivation questionnaires, observations, and documentation. The results showed that the use of digital interactive media significantly improved students' learning motivation. In the first cycle, the average student motivation score was 68, while in the second cycle, it increased to 85. This improvement indicates that digital interactive media can make learning more engaging, enhance student participation, and facilitate better understanding of the material. Therefore, digital interactive media is recommended as an innovative learning strategy to improve students' learning motivation at the junior high school level.